2021
DOI: 10.3389/fpsyg.2021.707500
|View full text |Cite
|
Sign up to set email alerts
|

Association of Attention Deficit/Hyperactivity Disorder With Events Occurring During Pregnancy and Perinatal Period

Abstract: Background: The relationship of events occurring during pregnancy and perinatal period with attention deficit/hyperactivity disorder (ADHD) is not clear. Thus, the focus of the current study was to examine the effects of events occurring during pregnancy and perinatal period on ADHD.Methods: A two-phase cross-sectional study was performed across 13 schools in Changsha and Yiyang cities from March to December, 2014. We preliminarily screened all students using CBCL and established the diagnosis using Mini Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The finding is supported by studies conducted elsewhere [ 39 , 78 , 79 ]. The possible explanation might be maternal complications during pregnancy might cause multi-organ damage including the central nervous system, which can affect fetal neurodevelopment and may predispose to ADHD [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding is supported by studies conducted elsewhere [ 39 , 78 , 79 ]. The possible explanation might be maternal complications during pregnancy might cause multi-organ damage including the central nervous system, which can affect fetal neurodevelopment and may predispose to ADHD [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis suggests that the offspring of women with a history of abortion were at higher risk of ASD. Regardless of ASD as a neurodevelopmental disorder, previous studies demonstrated a positive association between abortion and other neurodevelopmental disorders such as attention-deficit/hyperactivity disorder [ 25 , 26 ], intellectual disability [ 27 ], and cerebral palsy [ 28 ]. Since abortion is a common adverse pregnancy outcome, valid and robust evidence of its effect on adverse outcomes in children is a research need that can be addressed using large-scale prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that hypoxia can create long-term abnormalities of the dopaminergic system and even reduce the expression of the dopamine D2 receptor, hence increasing the risk of ADHD. In addition, current research indicates that hypoxia can change catechol-O-methyltransferase (COMT) gene expression; the COMT gene has been linked to ADHD or ADHD symptoms [ 23 ].…”
Section: Reviewmentioning
confidence: 99%